Mapping of deforestation and forest degradation associated with responsible drivers in the Man River Basin, Central India - Thakur, Jitendra (Geodesy and Cartography, 2022)
In developing countries, both deforestation and forest degradation are of serious environmental concern due to various driving factors. This can be more difficult to manage due to the lack of quality data and the unavailability of appropriate mapping techniques. Based on remote sensing data, this study examined an integrated approach to improve the mapping capability of forest change monitoring for data deficient areas. The study is carried out integrating ground-based information with Landsat 5 TM, Landsat 8 OLI and TIRS in the Man River Basin, India. The findings of the current study suggest that the integrated approach enhances the ability of modeling to estimate deforestation and forest degradation associated with responsible drivers, especially in countries such as India where grassroots data are infrequent.